2022
DOI: 10.1136/bmjopen-2021-051144
|View full text |Cite
|
Sign up to set email alerts
|

AVOID; a phase III, randomised controlled trial using indocyanine green for the prevention of anastomotic leakage in colorectal surgery

Abstract: IntroductionAnastomotic leakage (AL) is one of the major complications after colorectal surgery. Compromised tissue perfusion at the anastomosis site increases the risk of AL. Several cohort studies have shown that indocyanine green (ICG) combined with fluorescent near-infrared imaging is a feasible and reproducible technique for real-time intraoperative imaging of tissue perfusion, leading to reduced leakage rates after colorectal resection. Unfortunately, these studies were not randomised. Therefore, we prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 39 publications
0
11
0
1
Order By: Relevance
“…It has been suggested that RCTs might have some aws, such as sample size and endpoint selection [32]. Several RCTs are currently ongoing to prove the clinical bene t of routine use of ICG uorescence [33,34]. In this study, while operating time was signi cantly associated with AL incidence after laparoscopic rectal cancer surgery, male sex and tumor location tended to be associated with AL.…”
Section: Discussionmentioning
confidence: 64%
“…It has been suggested that RCTs might have some aws, such as sample size and endpoint selection [32]. Several RCTs are currently ongoing to prove the clinical bene t of routine use of ICG uorescence [33,34]. In this study, while operating time was signi cantly associated with AL incidence after laparoscopic rectal cancer surgery, male sex and tumor location tended to be associated with AL.…”
Section: Discussionmentioning
confidence: 64%
“…Nevertheless, this is yet to be proven in well-conducted and powered randomized control trials. Hopefully, the results of the AVOID study will provide the evidence needed to dissolve any ensuing skepticism on this modality [ 15 ]. A recently published Delphi consensus of international experts on the use of ICG further supported the use of ICG for anastomotic perfusion assessment (100% consensus reached), as well as issues such as timing and dosage of ICG for perfusion assessment during colorectal surgery [ 108 , 109 ].…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…One of these metanalyses [ 14 ] reported that the weighted mean rate of change in the surgical plan due to ICG imaging was 9.6% (95% CI 7.3–11.8). Currently, another phase III multicenter randomized controlled trial is being launched (NCT04712032; NL7502) [ 15 ] aiming to provide high quality evidence regarding the role of ICG in the reduction of clinically relevant ALs. The current literature reports that ICG assessment is a safe and rapid means of assessing anastomotic perfusion/bowel perfusion ( Figure 2 ) and may result in reduction of AL.…”
Section: Current Uses Of Icg In Colorectal Surgerymentioning
confidence: 99%
“…It has been suggested that RCTs might have some flaws, such as sample size and endpoint selection [ 33 ]. However, several RCTs are currently ongoing to prove the clinical benefit of routine use of ICG fluorescence [ 34 , 35 ], such as Essential Trial, whose results remain unpublished. In this study, while operating time was significantly associated with AL incidence after laparoscopic rectal cancer surgery, male sex and tumor location tended to be associated with AL.…”
Section: Discussionmentioning
confidence: 99%